2021
DOI: 10.1002/hrm.22052
|View full text |Cite
|
Sign up to set email alerts
|

Sixty years of discrimination and diversity research in human resource management: A review with suggestions for future research directions

Abstract: This article reviews discrimination and diversity research published in Human Resource Management (HRM) over the past 60 years. While discrimination and diversity are very different constructs, it is often informative to study them together, because when people recognize each other's diversity, this can result in bias, stereotyping, and discrimination. We conducted bibliographic searches for terms related to discrimination and diversity as well as a manual search through every title and abstract published in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 303 publications
1
43
0
1
Order By: Relevance
“…As labour market inequality and discriminatory practices come under growing scrutiny, normative pressure, broader social movements, legislation and regulatory oversight, employers have sought to boost the presence and inclusion of 'historically underrepresented' groups. This can be seen in a range of EDI pledges, policies and initiatives, as well as pro-diversity language, that seeks to attract specific groups of workers and/or emphasize the value of cultural diversity (Koellen 2021;Konrad et al 2006;Triana et al 2021;Yadav & Lenka 2020).…”
Section: Policy and Legislation Cuesmentioning
confidence: 99%
“…As labour market inequality and discriminatory practices come under growing scrutiny, normative pressure, broader social movements, legislation and regulatory oversight, employers have sought to boost the presence and inclusion of 'historically underrepresented' groups. This can be seen in a range of EDI pledges, policies and initiatives, as well as pro-diversity language, that seeks to attract specific groups of workers and/or emphasize the value of cultural diversity (Koellen 2021;Konrad et al 2006;Triana et al 2021;Yadav & Lenka 2020).…”
Section: Policy and Legislation Cuesmentioning
confidence: 99%
“…While there are policy and academic studies that examine employment discrimination based on religious expression or gender identity and sexual orientation, these types are relatively understudied in the literature, as compared to studies examining race or sex discrimination (Triana et al, 2021: p. 146). The impact of faith on the workplace is dramatically understudied in human resources (Héliot, Gleibs, Coyle, Rousseau, and Rojon, 2020; Messarra, 2014) and gender identity and sexual orientation are considered emerging areas in the literature (Triana, et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While there are policy and academic studies that examine employment discrimination based on religious expression or gender identity and sexual orientation, these types are relatively understudied in the literature, as compared to studies examining race or sex discrimination (Triana et al, 2021: p. 146). The impact of faith on the workplace is dramatically understudied in human resources (Héliot, Gleibs, Coyle, Rousseau, and Rojon, 2020; Messarra, 2014) and gender identity and sexual orientation are considered emerging areas in the literature (Triana, et al, 2021). In their 2021 survey of discrimination and diversity research published in Human Resource Management during the past 60 years, Triana, et al, found that 12 of 135 articles examines gender identity or sexual orientation and only one literature review examines religious identity at work, examining both U.S. and global populations (p. 146–147).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…An organization's performance and competitive advantage can enhance human resource practices [7]. The means by which to increase the efficiency of human resources are the competencies that [8] are characterized as knowledge, skills, abilities, or personality characteristics that affect a person's performance. Furthermore, [9] perceives them as the ability to behave in a way that meets work requirements in the organization's environment parameters while bringing the desired results.…”
Section: Introductionmentioning
confidence: 99%